The Effect of Job Stress and Motivation on Teachers’ Performance in Private Schools of Kathmandu Valley - Shrestha, Dal Bahadur (Journal of Rapti Babai Campus, 2026)
There are notable connections between teachers' performance with time pressure, workload, and motivation and other components of job stress. Statistical Package for Social Science was used to do quantitative analysis of data which is collected through a structured distributed via google forms to the target respondents of various schools. This study is focused on six demographic profiles which includes age, gender, academic qualifications, levels of teaching, marital status and teaching experience. In this study where r = 0.300, p < 0.01 indicates that more workload associated with teacher has positive effect on performance. Likewise, r = 0.456, p < 0.01 indicates that teachers perform better under moderate time pressure and r = 0.095 indicates that motivation factors associated to teachers has minimal positive effect on performance. In private schools, job stress of teachers seems to be a major factor contributing to performance and productivity. Therefore, employees need motivation and stress reduction strategies in the workplace to enhance their performance and productivity.